Función paterna en la estructura de personalidad de mujeres universitarias con hijos (2016)
Taking into account the psychoanalytical theory, the significance of the parental function in the personality structure and its relationship with the motherhood as one of the alternative for castration, and the national demographic and health inquiry, in Colombia; which allows us look the high level of unplanned pregnancy leading us to the problem question, which is the dynamic of the parental function into the personality of undergraduate women, who already are mothers?. This research was made by means of the study of a teacher with three children; taking into account as standard for the social inclusion she became mother in the middle of her university education and her pregnancy was an unplanned one. In the result, it was affirmed that the passive position of the father or a castrating father, for mark on the personality structure, such as feeling of minusvilia, insecurity,low tolerance for frustration before criticism or social opinions, conflicting relationships and stagnation in their love; with negative consequence in the social relations of friendship and feeling, unconsciously generating a demand for the love or the search for emotiona independence, which in the case of this investigation balance out with motherhood.